Sports medicine and new challenges for Olympic education: ethical and educational aspects - Di Pietro, B.; Colitti, P.; Isidori, E.; Pigozzi, F. (Medicina dello Sport, 2012)
The purpose of this article is two-fold. First, it discusses the importance of sports medicine as a human science which, through joint collaboration with education, can contribute to the spread of Olympic values in contemporary society, in accordance with rules and norms of medical care and those regulating the organization of sports activities. Through the use of bibliographic resources and a historic-hermeneutic methodology, the discussion will conclude that the birth of medicine in ancient Greece constituted a knowledge of sports centered on the therapéia of the body and mind of the athlete. As such, it represented a type of sophía that embodied a public ethics and a professional deontology, thus incorporating a pedagogical aspect. Hence, scholars can find the potential for translating into concrete actions the fundamental values of Olympic education. Second, the article examines the metaphysical aspect of legal rules. This basis ensures the functioning of rules as a stabilizing element in relationships between individuals. In this perspective, the boundary is drawn between legal and other types of rules. This theme will be developed as it concerns the ethics of legal rules and sports rules.